Crafting Success: Creative Management Techniques for Darul Ulum Sipaho Islamic Boarding School's Arabic Language Learning Program Implementation - Renni Hasibuan; Muhammad Jundi (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
The Modern Islamic Boarding School Darul Ulum Sipaho is a prominent educational institution that emphasizes its Arabic language program as one of its main strengths. To ensure the success of the Arabic language learning program, the boarding school implements specific strategies in managing the program's implementation. This research aims to reveal the strategies used by the boarding school in running the Arabic language program, particularly through the actuating management aspects that encompass communication, leadership, and supervision. The research findings indicate that: 1) The leadership style applied in the implementation of the Arabic language program in this boarding school reflects a wise combination of democratic and autocratic approaches, demonstrating the chairman's flexibility in facing various situations. 2) In the implementation of the Arabic language program in this boarding school, there are various types of communication, including vertical, horizontal, and lateral communication, both through face-to-face communication and official communication. 3) Supervision is conducted by involving direct observation, active feedback, and structured follow-up, the supervision and evaluation process in the implementation of the Arabic language program in this Islamic boarding school creates a collaborative dynamic aimed at ensuring sustainability, quality improvement, and the achievement of common goals. The implication of this research is the integration of flexible leadership, diverse communication, and collaborative supervision processes in the implementation of the Arabic language program at the boarding school can serve as an effective foundation for achieving sustainability, quality improvement, and shared success in organizational goals.